Autour du sens critique dans l’éducationaux médias musicaux - Angélica RIGAUDIÈRE (Tic & Société)
In France, music has been neglected through many years in media education. I suggest that this exclusion is related to the meaning of critical thinking in media education; a critical approach to music is hardly compatible with the informational paradigm that prevails in media education. However, since the turn of the century, sound and music occupy a more significant place in official documentation about media education. Considering the digital turn as a long-term phenomenon, the focus of this article is on the meaning of critical thinking and its changes in the professional discourse of music teachers in French secondary schools. Taste, active listening, aesthetic judgment, creation are all related to critical thinking. Applied to music, media education would be well advised to consider these concepts.